Unit Cost Analysis of Haemodialysis Services By Activity Based Costing Approach as a Strategy For Increasing Hospital Profits - Rista Agustin Margina; Gine Das Prena (Eduvest - Journal of Universal Studies, 2024)
One of the catastrophic diseases that is the focus of health insurance financing is kidney failure. Haemodialysis is a type of kidney replacement therapy for chronic kidney disease using special equipment. One method of financing haemodialysis procedures is the National Health Insurance Program. Hospitals, as health service providers for JKN participants, have an interest in the INACBG rates. Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 3 of 2023 concerning Health Service Tariff Standards in the Implementation of the Health Insurance Program, there are changes to tariffs for haemodialysis services. With the current tariff changes, single-use and re-use services are divided into two different tariffs. The research was conducted at Siloam Hospital Bali. The data taken is secondary data originating from the Financial Division of Siloam Hospital Bali, the Medical Records Department of Siloam Hospital Bali, and the Haemodialysis Department of Siloam Hospital Bali during the period January–April 2023. The data collected and the hypothesis formulated in this research will be tested using the MANOVA (Multivariate Analysis of Variance) test method, using SPSS software. The research results show that there is a significant difference in total costs for re-use and single-use haemodialysis services; there is a significant difference in the total INACBG rates per patient for re-use and single-use haemodialysis services and there is no significant difference in the difference between INACBG rates and total costs in re-use and single-use haemodialysis services.